L’efficacité du jeu Spelling Bee sur l’apprentissage du vocabulaire français des lycéens de SMA Kristen YSKI Semarang - Pradaiva Nabilla Cahya Camille; Aisyiah Al Adawiyah (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2025)
This study is based on the background of class XI students of YSKI Semarang Christian High School who have difficulty in doing question and answer in class due to lack of vocabulary mastery owned by students so that it has an impact on French language skills that are not in accordance with learning objectives. One solution is to use game-based learning media. Spelling Bee game is one of the methods that can be used to strengthen vocabulary in foreign language learning at school, especially French. The purpose of this study was to determine the application and effectiveness of Spelling Bee game in learning French vocabulary for grade XI students at YSKI Semarang Christian High School. The average post-test score in both classes was higher than the average pre-test score. In addition to the increase in the average score, the effect of the application of Spelling Bee game is also shown by t-test. Based on the results of the t-test conducted, the t-table is 1.684 while the t-count is 1.845, meaning that the t-count > t-table, so Ho is rejected and Ha is accepted. From the results of this study, it can be concluded that the Spelling Bee game is effective in learning French vocabulary of grade XI students of YSKI Semarang Christian High School.